Gut hormones, appetite suppression and cachexia in patients with pulmonary TB. - Suzanne W Chang; William S Pan; Daniel Lozano Beltran; Lizet Oleyda Baldelomar; Marco Antonio Solano; Iskra Tuero; Jon S Friedland; Faustino Torrico; Robert H Gilman (PLoS ONE)
Background Cachexia is a hallmark of pulmonary tuberculosis and is associated with poor prognosis. A better understanding of the mechanisms behind such weight loss could reveal targets for therapeutic intervention. The role of appetite-regulatory hormones in tuberculosis is unknown. Methods and findings 41 subjects with newly-diagnosed pulmonary TB (cases) were compared to 82 healthy controls. We measured appetite, body mass index (BMI), % body fat (BF), plasma peptide YY (PYY), leptin, ghrelin, and resistin for all subjects. Measurements were taken at baseline for controls and at treatment days 0, 30, and 60 for cases. Baseline appetite, BMI, and BF were lower in cases than in controls and improved during treatment. PYY, ghrelin, and resistin were significantly elevated in cases and fell during treatment. Leptin was lower in cases and rose with treatment. Appetite was inversely related to PYY in cases. High pre-treatment PYY predicted reduced gains in appetite and BF. PYY was the strongest independent predictor of appetite in cases across all time points. Conclusions Appetite-regulatory hormones are altered in TB patients. As hormones normalize during treatment, appetite is restored and nutritional status improves. High baseline PYY is an indicator of poor prognosis for improvement in appetite and nutrition during treatment. Wasting in TB patients may partly be mediated by upregulation of PYY with resulting appetite suppression.